PENEGAKAN SANKSI PIDANA DALAM PENANGGULANGAN KORUPSI PADA PERIZINAN PUBLIK - Nuarta, Nengah; Ketut Krisna Hari Bagaskara P (Jurusan Hukum Fakultas Dharma Duta Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2026)
Corruption in the licensing service sector is one of the vulnerable points of authority abuse in modern bureaucracy in Indonesia. This study systematically discusses corruption in public services through a criminal policy approach, so that law enforcement against corruption in public licensing can be analyzed structurally, normatively, and operationally. This research is a type of normative legal research based on the analysis of criminal law policy in handling corruption in the public licensing sector. The essence of preventing corruption in public licensing is multidimensional. It is not only a repressive action in the form of action against the perpetrator, but a preventive, corrective, and reconstructive process to build transparent, accountable, integrity-based governance, and responsive to public justice. The orientation of criminal law policy in eradicating corruption in licensing has shifted from a purely repressive paradigm to a transformational paradigm, namely the use of criminal law as a means of engineering governance. The success of enforcing corruption in licensing is not only determined by the severity of sanctions or the number of arrests, but by the state's success in building a public service system that is transparent, digital, accountable, and based on institutional integrity.